Evaluation of the Effect of Niosomal Nano-Carriers Containing Rosemary(Rosemary officinalis) Essential oil on Survival of KG-1 Cell Line of Acute Myeloid Leukemia - Najmah soltani; Narges Nikoonahad lotfabadi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2019)
Introduction: The use of nanotechnology in drug delivery to the cells can somewhat address some of the problems involved in the delivery of herbal medicines, including non-targeting and high oxidizing features. Therefore,this study aimed to investigate the niosomal nano-carriers containing Rosmarinus officinalisessential oil to improve itsphysicochemical characteristics and increase its antitumor properties.